Cover Image. (13th July 2020) - Slipets, Roman; Ilchenko, Oleksii; Mazzoni, Chiara; Tentor, Fabio; Nielsen, Line Hagner; Boisen, Anja
Abstract : The cover image is based on the Research Article Volumetric Raman chemical imaging of drug delivery systems by Roman Slipets et al., https://doi.org/10.1002/jrs.5869 .